The countervailing effects of competition on public goods provision: When bargaining inefficiencies lead to bad outcomes - Gottlieb, Jessica; Kosec, Katrina (International Food Policy Research Institute, 2018)
Political competition is widely recognized as a mediator of public goods provision through its salutary effect on incumbents’ electoral incentives. We argue that political competition additionally mediates public goods provision by increasing the inefficiency of legislative bargaining. These countervailing forces will produce a net negative effect in places with weak parties and low transparency – typical of many young democracies. We provide rigorous evidence from one such context, Mali, and then show results generalize to other weak party settings. Using panel data from Mali and a first differences model, we find a robust negative relationship between competition and local public goods. Tests of mechanisms corroborate our interpretation of this relationship as evidence that legislative bargaining inefficiencies are driving poor outcomes. This sheds light on why evidence of positive effects generally comes from more established democracies, and underscores the importance of both the electoral and legislative arenas in analyzing public goods provision.